Future directions of land consolidation to address global challenges and technological innovations - Demetriou, Demetris (My University, 2024)
Land consolidation is a primary land management approach that aims to achieve sustainable agricultural development. Land redistribution is a complex decision-making process that involves reallocating land parcels and ownership. Ideally, it involves the production of a number of alternative plans, which can be assessed using multi-criteria decision making (MCDM), to rank alternatives and select the "best" plan based on their performance. Currently, a deterministic approach (D-MCDM) is used for this purpose, which inherently ignores uncertainties and variabilities of both the scores for each criterion as well as the weights assigned to each criterion. Thus, a core research question is: What will be the ranking of alternative land redistribution plans if a stochastic multi-criteria decision-making (S-MCDM) approach is utilised? Hence, we have utilized a specific type of S-MCDM method called Stochastic Multi-criteria Acceptability Analysis (SMAA). SMAA is designed to deal with decision-making problems where there is uncertainty in the criteria weights, performance of alternatives, or both. The SMAA methodology was implemented using an open-source software called JSMAA. The comparison of outputs resulting from deterministic and stochastic MCDM showed different rankings for alternative plans. This suggests that the use of D-MCDM when uncertainties exist can lead to misleading decisions. This finding is important for land consolidation planners, decision-makers, and stakeholders involved in a project, because the "best" plan is one that satisfies the project objectives. Furthermore, other decision-making domains that involve uncertainties should be aware of the use of D-MCDM instead of S-MCDM.
Keywords: Land redistribution plans; Stochastic multi-criteria acceptability analysis (SMAA); Remote Sensing and Geoinformation